Analisis Model Tarikan Perjalanan Masyarakat ke Kawasan Perdagangan/Perbelanjaan Kota Bandar Lampung - Niatika, Uun; Sulityorini, Rahayu; Karami, Muhammad (Jurnal Rekayasa Sipil dan Desain, 2018)
The objectives of this research were to analyze the characteristics of person movements in the Pasar Tengah shopping area of Bandar Lampung City, the model of trip attraction using regression analysis method and variables influence the attraction of person movements to the commercial area of Bandar Lampung City. The roadside interview carried out at the internal cordon was designed to collect data. The questions were asked about the origin, destination and purpose of the journey, the mode of transport used by the travellers and others. The result shows that the variables influenced the trip attraction of the person to this commercial area including the number of people in each household (X4), motor vehicle ownership (X5), the volume of retail sales (X10) and the goods price (X11). The trip attraction model obtained from the research is Y = -2.447 + 0.233X4 + 0.511X5 + 0.267X10 + 0.236X11 with R2 = 0.863.